KINERJA KESATUAN PENGELOLAAN HUTAN WAY PISANG PROVINSI LAMPUNG PASCA UNDANG – UNDANG CIPTA KERJA - Febrian, Ardi; Wulandari, Christine; Kaskoyo, Hari; Bakri, Samsul (Jurnal Hutan Tropis, 2024)
The Way Pisang Forest Management Unit (FMU) has significant obligations and roles in overseeing forest areas at the ground level, including forest management and preparing forest management plans; forest utilization; forest use; rehabilitation and reclamation; and forest protection and nature conservation. Performance appraisals are completed to examine the progress of implementing forest management role at the site level. This research aims to provide a performance assessment of the Way Pisang FMU after the enforcement of the Job Creation Law (UUCK) using models and indicators from Forest Watch Indonesia version 2.0 which consists of 9 measures, 28 indicators and 62 quality components. The result shows that the forest management performance index value of Way Pisang FMU is at Medium category, which means that KPH Way Pisang is quite good at managing forest areas. However, there are yet a few rules that require improvement, namely area stabilization, government relations  and regulations, and investment mechanisms to ensure the optimization of operationalization of Way Pisang FMU in the site level of forest management.